A Bibliometric and Thematic Analysis of the Indian Journal of Marketing : A Study of 13 Years - Joshi, Nisarg A.; Joshi, Mruga; Trada, Sandip (Indian Journal of Marketing, 2024)
Purpose : It is necessary to do a bibliometric assessment of the Indian Journal of Marketing (IJM). This highly regarded peer-reviewed and referenced publication disseminates genuine and empirical research in marketing across the broad purview of the management domain. A bibliometric overview, diagrammatic mapping, and thematic analysis of IJM from 2010 to 2022 were the main objectives of this study. Methodology : A total of 731 papers published in IJM were examined in this bibliometric analysis. We took the necessary information out of Scopus and saved it as CSV. Biblioshiny was used to do bibliometric analysis. Using methods like co-citation, co-authorship, and co-occurrence, Vosviewer software was used to visualize the data. Findings : The number of papers published was trending downward, but the number of citations obtained was trending upward. The most well-known and highly referenced authors in IJM are respected figures in the field. Due to Indian Journal of Marketing being chosen as the preferred forum for their research, developing nations and the institutions connected with them made comparatively large contributions to the journal. In terms of author, nation, and institute co-authorship patterns, this is accurate. The journal took into account the majority of marketing-related issues, even some that had just developed, as evidenced by highly frequent terms and keyword co-occurrence patterns. Practical Implications : The findings of this study may help the Indian Journal of Marketing editorial board and editorial team make decisions about its future direction and may also make it easier for practitioners and researchers who are interested in the subject of marketing to interact with and contribute to the journal. Originality : The current study provided insights into various new and recent facets associated with the area of Indian Journal of Marketing. Previously, similar analysis with the bibliometric technique has rarely been done with the present Scopus database for the journal.